Organisation of physical education at the university based on students' constitutional types and health groups - M. M. Kolokoltsev; S. S. Iermakov; N. V. Tretyakova (Russian State Vocational Pedagogical University, 2019)
Introduction. Today, the significant direction of scientific search in the field of health preservation is to study the interrelation of functional characteristics and motor skills of students of different constitutional types and health groups. Specific morphological and physiometric characteristics of an organism and belonging to a certain somatotype should be taken into account when organising physical training in higher education institutions.The aim of the research was to establish the degree of correlation of motor and functional characteristics of an organism of students with different constitutional types and health groups in order to improve an algorithm of planning and effective safe implementation process of physical training in a higher education institution.Methodology and research methods. Male-students (n = 1300) aged 17-20 years old of the 1st (n = 1012) and 2nd(n = 288) functional groups of health were examined. Constitutional types were determined according to M. V. Chernorutsky's scheme with the calculation of values of Pignet index and Robinson index. Methods of the statistical analysis with the application of StatSoft Statistica 6.1 and Microsoft Excel programmes were used to process the obtained results in the process of diagnostics. The reliability of distinctions of average values was estimated by means of parametrical methods with the calculation of Student's t-test.Results and scientific novelty. Motor features and functional characteristics of the cardiorespiratory system and physiometric parameters of firstand secondyear students (engaged in the programme of academic discipline "Elective Courses on Physical Culture and Sport" atIrkutskNationalResearchTechnicalUniversity) are recorded and considered. Reliable differences in the values of indicators of motor tests and functional characteristics of organisms of young people with different constitutional types are identified. In both health groups, the experiment allowed authors to reveal higher physical and functional preparedness of young men of normosthenic and asthenic constitutional types compared to their fellow hypersthenic students. Motor characteristics and functional reserve capacities of the cardiorespiratory system were higher in normosthenic and asthenic students of the 1st functional group in comparison with the representatives of the 2ndfunctional group of the same constitutional types. The conclusion is drawn on close interrelation of somatotypes with motor and functional characteristics of organisms of students engaged in physical culture.Practical significance. The research material and results contribute to the elaboration and development of the methodology of individually differentiated physical training of students in higher education institution.